Regionális logisztikai rendszerek - Veres, Lajos (Közép-Európai Közlemények, 2009)
The spread of regionalisation gives new tasks to the regional level. Effective solutions for the management of these tasks require the construction of new networks and regional logistics applications. The essay introduces the logistics bases of the operation of waste management and the regional innovation systems during the regional level organisation of public services.